Acute toxicity: a comparative study on the methanol extract of three selected plants reported to have anticancer properties - Oladipo Miriam Oluchi; Bamidele Fatai , Oladipo; Henry Chukwuebuka , Nwankwo; Joel A , Bosha; Alhaji Saganuwan , Saganuwan; Patrick Azubuike, Onyeyili (International Journal of Pharmacology and Toxicology, 2024)
Background: An acute toxicity study evaluates the harmful effects of substances absorbed through any route and utilizes parameters like LD50 to assess toxicity. While mortality is commonly used as a primary endpoint, considering signs of toxicity is crucial as they indicate adverse effects on internal organs, which can lead to lasting damage or death.Objectives: This study compares the acute toxicity of three medicinal plants with anticancer properties, highlighting the importance of understanding their safety profiles despite their therapeutic potential.Methods: The acute toxicity of methanol extracts from Curcuma longa rhizome, Datura metel fruits, and Phoenix dactylifera fruits in rats were compared to determine the safest of the three plant extracts. A new modified method was employed to estimate the Lowest Observed Adverse Effect Level (LOAEL) and the No Observed Adverse Effect Level (NOAEL). Each dose level involved three (3) rats, with a default dose progression of log 3.2 if the animal dies or a sign of toxicity is observed.Results: While no mortality occurred at a dose of 5000 mg/kg body weight for any extract, signs of toxicity were observed. Histological changes were noted in animals without apparent signs of toxicity, challenging the assumption that LD50 values exceeding 5000 mg/kg body weight indicate non-toxicity. Threshold dose analysis revealed differences in toxicity among the extracts. Curcuma longa rhizome methanol extract demonstrated the highest safety margin.Conclusion: These findings emphasize the importance of considering signs of toxicity alongside mortality in acute toxicity assessments.